Human CD8+ CTL specific for the mycobacterial major secreted antigen 85A. - Smith, S; Brookes, R; Klein, MR; Malin, A; Lukey, P; King, A; Ogg, G; Hill, A; Dockrell, H (2000)
The role of CD8(+) CTL in protection against tuberculosis in human disease is unclear. In this study, we stimulated the peripheral blood mononuclear cells of bacillus Calmette-Guérin (BCG)-vaccinated individuals with live Mycobacterium bovis BCG bacilli to establish short-term cell lines and then purified the CD8(+) T cells. A highly sensitive enzyme-linked immunospot (ELISPOT) assay for single cell IFN-gamma release was used to screen CD8(+) T cells with overlapping peptides spanning the mycobacterial major secreted protein, Ag85A. Three peptides consistently induced a high frequency of IFN-gamma responsive CD8(+) T cells, and two HLA-A*0201 binding motifs, P(48-56) and P(242-250), were revealed within the core sequences. CD8(+) T cells responding to the 9-mer epitopes were visualized within fresh blood by ELISPOT using free peptide or by binding of HLA-A*0201 tetrameric complexes. The class I-restricted CD8(+) T cells were potent CTL effector cells that efficiently lysed an HLA-A2-matched monocyte cell line pulsed with peptide as well as autologous macrophages infected with Mycobacterium tuberculosis or recombinant vaccinia virus expressing the whole Ag85A protein. Tetramer assays revealed a 6-fold higher frequency of peptide-specific T cells than IFN-gamma ELISPOT assays, indicating functional heterogeneity within the CD8(+) T cell population. These results demonstrate a previously unrecognized, MHC class I-restricted, CD8(+) CTL response to a major secreted Ag of mycobacteria and supports the use of Ag85A as a candidate vaccine against tuberculosis.